SALURAN IRIGASI KOTTA LEIDING KOTA MAGELANG (Tinjauan Bentuk, Jalur, dan Latar Belakang) - , DANAR PRASETYO AJI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Topic : Kotta Leiding Irrigation Canal is an artificial application of water to the land or soil located in the centre of Magelang. One of its uniqueness is in a particular lane, the canal is located higher than the ground. In addition, the existance of arch construction, which has function as an aquaduct bridge and opening access road, makes this canal is interesting to review especially in perspective of form and lane and its establishment background. Problem and Purpose : In this research, the problem is to figure out what form, lane and establishment backgound of Kotta Leiding. Whereas the purpose is to give a description about form, lane and establishment background of Kotta Leiding. This research is expected to give broader knowledge about irrigation technology and as an effort to preserve archaeological heritage in Magelang. Method : This research is using qualitative methods with inductive reasoning and descriptive. While applying three analysis, spatial analysis, architecture analysis and historical analysis. Conclusion : Section form of Kotta Leiding Irrigation Canal is devided into two, trapezium and rectangular. The lane of Kotta Leiding Irrigation Canal is following main road of Magelang. While establishment of Kotta Leiding background is as an irrigation infrastructure which is located higher than the ground and can not be reached from two rivers, Kali Bening and Kali Manggis. It is expected for related government institution to overcome lots of problems regarding Kotta Leiding canal in order to keep itas an archaeological heritage works well.